Investigating Endemic Alpine Communities of Papaver corona-sancti-stephani and Cerastium lerchenfeldianum in the Southern Carpathians - Claudia Biță-Nicolae; Daniela Mogîldea; Oliviu G. Pop (Diversity)
The high-elevation calcareous screes of the Southern Carpathians are ecologically important habitats characterised by extreme environmental conditions. These habitats support specialised plant communities, including endemic and relict species, shaped by climatic, edaphic and biogeographic factors. This study examines three scree vegetation communities in the Bucegi, Piatra Craiului and Făgăraș massifs to assess species composition, ecological strategies and environmental influences. Phytosociological surveys were carried out using the Braun-Blanquet method, diversity indices (species richness, Simpson indices and species evenness) and multivariate analyses, including ANOSIM (ANalysis Of SIMilarities), SIMPER (Similarity Percentage method) and PCA (Principal Component Analysis), and were applied to evaluate species–environment relationships. A total of 62 vascular plant species were recorded, with Caryophyllaceae and Asteraceae as the dominant families. Differences in lifeform composition and species distribution between the massifs were related to variations in soil moisture, nutrient availability and climatic conditions. The results highlight the role of calcareous substrates in supporting alpine endemism and underline the influence of abiotic stress on community structure. Conservation efforts should prioritise these fragile ecosystems, especially as climate change and human activities increase pressure on high-elevation habitats. The study contributes to a broader understanding of the Carpathian alpine flora and its biogeographic connections with other European mountain systems, and it highlights the need for targeted conservation strategies to preserve biodiversity in these vulnerable environments.